Implementation of the City Without Slums Program in Makassar City - Aslinda Aslinda; Muhammad Luthfi Siraj; Muhammad Ikramullah Akmal (Jurnal Office, 2022)
The slum area in the city of Makassar is in the heavy slum category, namely 288.85 Ha which is divided into 36 sub-districts out of 127 sub-districts in the city of Makassar. This research was conducted aiming to find out how the Implementation of the City Without Slums Program in Makassar City. The research method used is a qualitative approach with a focus on implementation theory by G. Shabbir Cheema and Dennis A. Rondinelli (1983). Sources of research data used secondary data and primary data with data collection techniques of observation, interviews and documentation as well as data analysis techniques used were data collection, data condensation, data presentation and variation/conclusion. The research results are Of the four variable parameters for implementation success, three variables were good and one variable was considered not well implemented, ie 1. The condition of the environment is not good, from a physical perspective, there have been achievements in reducing slum areas in several sub-districts such as Makassar, Ujung Pandang and Pannampu. However, there have been no socio-cultural changes in the community in the slums in Macassar. 2. Relations between organizations are going well, in this case the actors involved are trying to strengthen institutions through communication and coordination channels carried out between stakeholders involved from the government, and the community and industry in innovating the area program without slums. 3. Organizational resources are running well because they are supported by qualified human resources with the expertise and knowledge to create programs for coaching and socialization of healthy living and environmentally friendly programs. Financial resources have also been utilized as well as possible in accordance with the urgency and needs of the sub-district. 4. The Characteristics and Skills of the Executing Agent are going well, in this case the executors in this case the BKM and the community involved in the work are trained both administratively, financially and technically for implementation in the field.